Desain dan Kinerja Alat Pengolahan Bioetanol Model Baristand untuk Menghasilkan Bahan Bakar Etanol [Design and Performance of Bioethanol Processing Tool Baristand Model to Produce Fuel Grade Ethanol] - Nicolas Tumbel; Supardi Manurung; Abnery Lay (Buletin Palma, 2016)
The development of renewable energy sources such as bioethanol was a major consideration, because of dwindling of unrenewable energy and increasing of energy needed. Utilization ofenergy from bioethanol was environmental friendly compared to fossil fuel. The objective of this research was to design small-scale bioethanol processing unit to produce bioethanol as a fuel or FGE which easily to be operated. The research was conducted at the Laboratory and Workshop of Research and Standardization of Industrial Institute Manado, and Equipment Engineeringof Indonesian Palms Crops Research Institute during 2013. The design of this machinery was based on to bioethanol processing unit through evaporator system-double distillation, and dehydration unit of bioethanol equipmet using molecular sieve zeolite with vacuum swing absorption techniques.Processing of FGE was equipped with controlled of temperature heating and utilization of molecular sieve for dehydrator column, processing. The process was evaluated for three times. The observed variables were design of tools (components, varianceof the operating unit temperature), and performance tools (working time, a flow rate of bioethanol, yield,  losses and quality of the product). The datas were analysis by descriptive method. The results showed that, the designed bioethanol processing tool has some main components such as evaporator tank, dehydrator column, and a distillation column. FGE was made by using bioethanol 90% as raw materials, temperature of heating operating (evaporator tank at 78-82ºC, dehydrator column around 76-90ºC, and distillation column about 25-35ºC. Theresulted FGE contains 99.88% of ethanol and yield reach to 92.13%. The FGE was visually clear and bright appearance, no deposits and debris. Bioethanol processing tools of Baristand model was more suitable to be used for farmer groups or small and medium level. ABSTRAKCadangan minyak bumi yang makin menipis dan makin meningkatnya kebutuhan energi serta dampak pencemaran lingkungan penggunaan energi dari minyak bumi, telah mendorong pengembangan sumber energi  terbarukan antara lain bioetanol. Tujuan penelitian untuk mendesain unit pengolahan bioetanol skala kecil  untuk menghasilkan bioetanol sebagai bahan bakar atau Fuel Grade Ethanol (FGE) yang praktis dioperasikan. Penelitian dilaksanakan pada Tahun 2013, di Laboratorium dan bengkel Balai Riset dan Standardisasi Industri Manado serta Bengkel Rekayasa Alat Balai Penelitian Tanaman Palma.  Desain alat didasarkan pada alat pengolahan bioetanol dari aren sistem evaporator-destilator ganda,  dan alat dehidrasi bioetanol menggunakan saringan molekuler zeolit dengan teknik vacuum swing absorbtion. Pengolahan FGE dengan suhu pemanasan terkontrol dan menggunakan saringan molekuler pada kolom dehidrator, proses pengolahan dilakukan  sebanyak tiga kali. Pengamatan terdiri atas: desain alat (komponen alat, keragaman suhu unit operasi), dan kinerja alat (waktu kerja, laju alir bioetanol, rendemen, kehilangan hasil, dan mutu produk). Analisis data secara deskriptif. Hasil penelitian menunjukkan bahwa alat pengolahan bioetanol yang didesain dengan komponen utama adalah tangki evaporator, kolom dehidrator, dan kolom destilator.  Pengolahan FGE menggunakan   bahan baku bioetanol  kadar 90%, suhu pemanasan unit operasi, yakni tangki evaporator 78-82ºC, kolom dehidrator 76-90ºC, dan kolom destilator 25- 35ºC. FGE yang dihasilkan berkadar etanol 99,88% dan rendemen 92,13%. FGE memenuhi syarat mutu dan secara visual kenampakan jernih dan terang, tidak ada endapan dan kotoran. Alat pengolahan bioetanol model Baristand ini, lebih sesuai penggunaannya untuk kelompok tani atau Usaha Kecil Menengah.